Developing a real-time PCR assay based on multiplex high-resolution melt-curve analysis: a pilot study in detection and discrimination of soil-transmitted helminth and schistosome species. Issue 13 (28th August 2018) - Cunningham, Lucas J.; Stothard, J. Russell; Osei-Atweneboana, Mike; Armoo, Samuel; Verweij, Jaco J.; Adams, Emily R.
Abstract: With the push towards control and elimination of soil-transmitted helminthiasis and schistosomiasis in low- and middle-income countries, there is a need to develop alternative diagnostic assays that complement the current in-country resources, preferably at a lower cost. Here, we describe a novel high-resolution melt (HRM) curve assay with six PCR primer pairs, designed to sub-regions of the nuclear ribosomal locus. Used within a single reaction and dye detection channel, they are able to discriminate Ancylostoma duodenale, Necator americanus, Strongyloides stercoralis, Ascaris lumbricoides, Trichuris trichiuria and Schistosoma spp. by HRM curve analysis. Here we describe the primers and the results of a pilot assessment whereby the HRM assay was tested against a selection of archived fecal samples from Ghanaian children as characterized by Kato–Katz and real-time PCR analysis with species-specific TaqMan hydrolysis probes. The resulting sensitivity and specificity of the HRM was 80 and 98.6% respectively. We judge the assay to be appropriate in modestly equipped and resourced laboratories. This method provides a potentially cheaper alternative to the TaqMan method for laboratories in lower resource settings. However, the assay requires a more extensive assessment as the samples used were not representative of all target organisms.